Benchmarking of postgraduate programmes in education in Malaysia - Nordin, Mohamad Sahari; Zainuddin, Ahmad Marzuki; Ismail, Nik Ahmad Hisham; Abdul Rashid, Adnan (IIUM Press, International Islamic University Malaysia, 2009)
Introduction: Of late education organisations have been held accountable to address quality-related questions. EveI)' institution of higher education is subjected to an increasing demand for quality assurance. the underlying concern being the degree to which the "totality of the features aad characteristics of the organisation's product or service bear on its ability to satisfy stated or implied needs" (International Standard Organisation 1986 definition. emphasis added). This means that higher earning institutions are expected to deliver products and services at some acceptable level of utility or benefit, specifically with respect to their core business teaching and learning. To address this pressing concern, education organisations have been assessing themselves by asking questions such as, "(1) How well are we doing compared to others, (2) how good do we want to be, (3) who is doing it the best, (4) how do they do it, (5) how can we adapt what they do in our institution, and (6) how can we be better thaa the best?" (Alslele, 1995: 2).